2017
DOI: 10.1080/14992027.2017.1370139
|View full text |Cite
|
Sign up to set email alerts
|

Programming characteristics of cochlear implants in children: effects of aetiology and age at implantation

Abstract: Aetiology and age at implantation had significant effects on T-levels and C-levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…There could be confounding factors which affected the educational status of enrolled patients even though the participants are highly homogeneous in the type of deafness and age at implantation. The most important variable is the age at the operation, with evidence from numerous studies [7-9]. In this study, age at the operation was controlled by enrollment criteria of under 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…There could be confounding factors which affected the educational status of enrolled patients even though the participants are highly homogeneous in the type of deafness and age at implantation. The most important variable is the age at the operation, with evidence from numerous studies [7-9]. In this study, age at the operation was controlled by enrollment criteria of under 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…We found that: Clinical practice is consistent across sites, with most CIs being programmed according to default values recommended by the manufacturer. The proportion of non-default settings in pulse width, stimulation rate, number of active electrodes and number of maxima was higher in children with auditory nerve deficiency or cochlear lesions, compared to children without those conditions (Incerti et al, this issue). Children with cochlear structural and/or neural lesions required significantly higher current levels for threshold and comfortable levels (T- and C-levels), as compared to children without those conditions.…”
Section: Summary Of Findingsmentioning
confidence: 96%
“…In first studies, the automatic fitting is equivalent to the original fitting. Thus the results are very promising for a future AI-based fitting of an audio processor [102].…”
Section: ▪ Fitting Based On Electrophysiological Measurementsmentioning
confidence: 80%
“…Fitting in pediatric patients is usually much more time-consuming than in adults and further encompasses numerous social and treatment-related aspects. In addition, electrophysiological fitting methods play a crucial role, in particular the intraoperative measurement of the stapedius reflex threshold and the ECAP measurement [102]. The parameter setting of the audio processor in children is a highly responsible activity that can only be performed with vast experience because it influences decisively the entire development of hearing and speaking of a child.…”
Section: Fitting In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation